2020
DOI: 10.1093/mnras/staa3702
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the young AU Mic system with SPIRou: large-scale stellar magnetic field and close-in planet mass

Abstract: We present a velocimetric and spectropolarimetric analysis of 27 observations of the 22-Myr M1 star AU Microscopii (AU Mic) collected with the high-resolution YJHK (0.98–2.35 μm) spectropolarimeter SPIRou from 2019 September 18 to November 14. Our radial velocity (RV) time-series exhibits activity-induced fluctuations of 45 m s−1 rms, ∼3 times smaller than those measured in the optical domain, that we filter using Gaussian Process Regression. We report a 3.9σ detection of the recently discovered 8.46 -d transi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
98
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 104 publications
9
98
1
Order By: Relevance
“…Figure 2 shows the position of the planets orbiting V1298 Tau in a mass-radius diagram compared to the known population of exoplanets. Similar to the case of AU Mic b 9 -the only other exoplanet of similar age with a mass measurement -the mass-radius relation of the planets orbiting V1298 Tau resembles that of the planets of our Solar System and of the general population of known transiting exoplanets.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Figure 2 shows the position of the planets orbiting V1298 Tau in a mass-radius diagram compared to the known population of exoplanets. Similar to the case of AU Mic b 9 -the only other exoplanet of similar age with a mass measurement -the mass-radius relation of the planets orbiting V1298 Tau resembles that of the planets of our Solar System and of the general population of known transiting exoplanets.…”
supporting
confidence: 55%
“…These theoretical expectations remain untested to date, despite the increasing number of exoplanetary discoveries, as the detection and characterisation of very young planets is extremely challenging due to the intense stellar activity of their host stars 3, 4 . However, the recent discoveries of young planetary transiting systems allow to place initial constraints on evolutionary models [5][6][7][8][9] . With an estimated age of 20 million years, V1298 Tau is one of the youngest solar-type stars known to host transiting planets: it harbours a multiple system composed of two Neptune-sized, one Saturn-sized, and one Jupiter-sized planets 10,11 .Here we report the dynamical masses of two of the four planets.…”
mentioning
confidence: 99%
“…for f spot being the spot filling factor estimated at 20% based on magnetic activity (Klein et al 2021) and F spot /F phot being the flux fraction between the spots and the photosphere. The latter can be estimated assuming a blackbody flux for each of the two components, where the photospheric temperature is T phot = 3700 K and the spots' temperature is estimated at 86% of the photospheric value in M1 stars (Rackham et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This Neptune-size planet is in a 8.5-d prograde orbit aligned with the stellar rotation axis (Martioli et al 2020;Hirano et al 2020;Palle et al 2020). While Plavchan et al (2020) only reported an upper limit on the mass of AU Mic b, Klein et al (2021) measured 17.1 +4.7 −4.5 M ⊕ thanks to infrared observations secured with the SPIRou spectropolarimeter (Donati et al 2020). Plavchan et al (2020) has also reported the detection of an isolated transit event of a second possible candidate planet, hereafter referred to as AU Mic c.…”
Section: Introductionmentioning
confidence: 98%
“…The orbital period is generally recovered with a high degree of confidence but the semi-amplitude is only recovered at the 5σ level for planets with semi-amplitude above 1 m s −1 . young pre-main-sequence stars V830 Tau (Donati et al 2016) and AU Mic (Klein et al 2020). In both studies, they were able to detect and characterize planetary signals with amplitudes five times smaller than the intrinsic RV variations.…”
Section: Synthesized Rvsmentioning
confidence: 99%